Microstructure, mechanical properties and low temperature degradation resistance of 2Y-TZP ceramic materials derived from nanopowders prepared by laser vaporization. Issue 9 (September 2015) - Smirnov, Anton; Kurland, Heinz-Dieter; Grabow, Janet; Müller, Frank A.; Bartolomé, José F.
Abstract: Starting from commercially available powders of tetragonal zirconia polycrystals (TZP) doped with 3 mol% yttria (Tosoh grade TZ-3YS-E) and yttria-free monoclinic zirconia (Tosoh grade TZ-0) powders with an overall Y2 O3 content of 2 mol% (2Y/TZP) were fabricated by CO2 laser vaporization (LAVA) and wet mixing, respectively. The obtained powders were compacted by spark plasma sintering. The influence of the Y 3+ distribution on the mechanical properties and on the low temperature degradation (LTD) of the obtained ceramics was investigated. 2Y/TZP ceramics sintered from LAVA nanoparticles showed significantly enhanced mechanical properties and improved LTD resistance due to the homogeneous yttria and grain size distributions in the ceramic structure. For the first time, the present research has demonstrated the effectiveness and reproducibility of the LAVA process for the preparation of tailored zirconia nanopowders enabling microstructural homogeneity and therefore optimized mechanical properties and degradation resistance of Y-TZP ceramics.